Differential Macrophage Response to Slow- and Fast-Growing Pathogenic Mycobacteria. (18th May 2014) - Helguera-Repetto, A. Cecilia; Chacon-Salinas, Rommel; Cerna-Cortes, Jorge F.; Rivera-Gutierrez, Sandra; Ortiz-Navarrete, Vianney; Estrada-Garcia, Iris; Gonzalez-y-Merchand, Jorge A.
Abstract : Nontuberculous mycobacteria (NTM) have recently been recognized as important species that cause disease even in immunocompetent individuals. The mechanisms that these species use to infect and persist inside macrophages are not well characterised. To gain insight concerning this process we used THP-1 macrophages infected with M. abscessus, M. fortuitum, M. celatum, and M. tuberculosis . Our results showed that slow-growing mycobacteria gained entrance into these cells with more efficiency than fast-growing mycobacteria. We have also demonstrated that viable slow-growing M. celatum persisted inside macrophages without causing cell damage and without inducing reactive oxygen species (ROS), as M. tuberculosis caused. In contrast, fast-growing mycobacteria destroyed the cells and induced high levels of ROS. Additionally, the macrophage cytokine pattern induced by M. celatum was different from the one induced by either M. tuberculosis or fast-growing mycobacteria. Our results also suggest that, in some cases, the intracellular survival of mycobacteria and the immune response that they induce in macrophages could be related to their growth rate. In addition, the modulation of macrophage cytokine production, caused by M. celatum, might be a novel immune-evasion strategy used to survive inside macrophages that is different from the one reported for M. tuberculosis .